Safety of simultaneous colon and liver resection for colorectal liver metastases - Stojanović Miroslav; Stanojević Goran; Radojković Milan; Zlatić Aleksandar; Jeremić Ljiljana; Branković Branko; Jovanović Milan; Kostov Miloš; Zdravković Miodrag; Milić Dragan (Vojnosanitetski Pregled)
Background/Aim. Surgical strategy for the treatment of resectable synchronous hepatic metastases of colorectal cancer (CRC) remains controversial. The aim of this study was to assess safety of simultaneous colon and liver resections and the direct effects of this type of treatment upon morbidity and mortality of the patients with synchronus hepatic metastases of CRC. Methods. Intraoperative and postoperative data of 31 patients with simultaneous liver and colorectal resection were compared with the data of 51 patients who had undergone colon and hepatic resection in the staging setting. Analyzed were demographic data, number of metastases, type of the liver resection, operation time, intraoperative blood loss, percentage of postoperative complications, morbidity and mortality and length of hospitalisation. Results. In the group of the patients operated simultaneously 5 hepatectomies, 3 sectionectomies, 2 trisegmentectomies, 3 bisegmentectomy, 6 segmentectomies, and 12 metastasectomies were combined with colon resection. In this group operation time (280 vs. 330 minutes) and intraoperative blood loss (450 vs. 820 ml) were lower than those in the two staged operation group. Postoperative complication rate was lower in the simultaneous group (19.35%) than in the two-staged operation group (19.60%), without statistical significance. There was no hospital mortality in both groups. The patients having simultaneous resection required fewer days in the hospital (median 10.2 days) than the patients undergone operation in the two stage (18.34 days). Conclusion. By avoiding a second laparotomy, overall operation time, blood loss, hospital stay and complication rate are reduced with no change in hospital mortality, so simultaneous colon and hepatic resection performed by the competent surgeons are safe and efficient for the treatment of synchronous colorectal liver metastases.